Benthic Foraminifera as Bio-Indicators of Trace Element Pollution at St. Martin’s Island, Bangladesh - Saha, Subrota Kumar; Tushar, Mahmud Al Noor; Shemu, Tamanna Meheran; Singh, Sonjita; Eva, Ishrat Jahan; Ali, Sheikh Romjan (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
Benthic Foraminifera occupied all marine environments. The practice of utilizing benthic foraminifera for monitoring the state of the marine environment has garnered widespread recognition all over the world. Changes in foraminiferal assemblage indicate the level of environmental stress. The prime concern of the present research is to evaluate the abundance and distribution of benthic foraminifera stress and how anthropogenic stresses affect their diversity in St. Martin's Island, Bangladesh. About 250 foraminifera specimens were collected, of which 22 species, 19 genera, and 17 families of predominantly benthic provenance were recognized. Astrorhiza holds the first position in order of relative abundance and frequency of occurrence followed by the Elphidium, Robulus, and Eponoides. The stress-tolerant and heterotrophic genera (Quinqueloculina, Elphidium, Ammonia, Trochammina) dominated the sensitive or symbiont genera (Calcarina, Operculina, Cibicides, Nummulites). Analysis of various diversity indices reveals that the northern part of the island near the boat terminal shows a lower diversity of benthic foraminifera. The southern part of the island shows moderate diversity indicating less pollution. For the investigation of the Foraminiferal shell, in addition to statistical computing, SEM (Scanning Electron Microscopy), EDX (Energy Dispersive X-ray Analysis), and XRD (X-ray Diffraction) analyses have been utilized. From the EDX analysis, it has been found that lower oxygen (O) with a weight range of (36.51-53.71%) and calcium (Ca) with a weight range of (30.44-53.38%) are the primary components of the foraminifera test. The shells also contain higher percentages of trace elements such as silicon (Si), magnesium (Mg), iron (Fe), chlorine (Cl), sodium (Na), aluminum (Al), and manganese (Mn). Anthropogenic activity is the main source of these trace elements, which clearly demonstrates the island's environmentally stressed condition. The intrusion of these elements in the benthic foraminiferal shell indicates they react to anthropogenic contaminants. These exogenous trace elements are responsible for particular morphological distortion of foraminifera shells which are also observed in St. Martin’s Island. The outcomes from the current research will build a foundation for future researchers focusing on anthropogenic impact assessment and sustainable coastal management in Bangladesh. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 12(2), 2023, P 1-14